Kewenangan Pemerintah Daerah dalam Hak Pengelolaan Tanah Sebagai Barang Milik Daerah - Syeputri, Fazrianita; Hartati, Hartati; Priskap, Ridham (Universitas Batanghari Jambi, 2025)
Although the provincial government is legally able to manage regional assets, there have been numerous instances of abuse of this power, including the following: the total disregard for regional assets; the misuse of rights granted by the regional government to access these assets; and the pursuit of private interests at the expense of the region and its residents. Jambi District Court's Decision Regarding Peace Deed No. 43 / Pdt.G / 2024 / PN Jmb.The goals of this research project are: 1) To learn about and assess the impact of regional asset regulation on the power of regional governments over land management rights 2) Determine and assess the authority of the regional administration to manage land as a resource for the area. This study used normative legal research methods including a statutory approach, a conceptual approach, and a case approach to achieve its aims. There are three levels of legal resources gathered: primary, secondary, and tertiary. Inventorying, systematizing, and interpreting the acquired legal materials constituted the process of analysis. Final findings from the study: 1) Various laws and regulations in Indonesia control the jurisdiction of regional governments in land management rights as regional property. These include Law Number 23 of 2014, Government Regulation Number 27 of 2014, Law Number 5 of 1960, and Regulation of the Minister of Home Affairs. 2. Mechanisms that strive to guarantee the effective, transparent, and accountable administration of public assets are an integral part of the responsibility of regional governments in land management rights as regional property. Important aspects of regional government accountability related to land management include: Asset management reports, supervisory audits, transparency and openness of information, the role of the DPRD, good governance, and sanctions for violations.